Pengawasan BPK Dalam Mewujudkan Pengelolaan Keuangan Daerah Yang Bebas Korupsi - Bachrul Amiq (Fakultas Hukum Universitas Mataram, 2016)
As the country's financial supervisory institutions / regions that are external to make the CPC as an institution that is very strategic in order to realize financial management area that is free of corruption. Combating corruption is not enough to rely on law enforcement officials, the police, the AGO and the KPK. Especially if done with no underlying advance by the CPC recommendations, a potential cause of criminalization on the area of financial management officer and it is very harmful. Supposedly the issue of errors in the financial management area has been completed if the local government officials have been corrected in accordance with the recommendation of the CPC, and it should no longer be done on the basis of criminal law enforcement. This is important in the context of legal protection against officials of the regional finance manager criminalization measures.